(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
The aims of the research were to provide a base-line for interpreting and documenting future changes in vegetation cover. Base maps such as navigation map issued by Dishidros, the department of transportation year 1912 and 1917, and map of proposed Bintuni bay natural reserved issued by Biphut, Forestry Department year 2000, were compared to Landsat TMS images from 1989, 1999, and 2002 to evaluate changes in coastline: significant changes in land formation due to accretion and erosion were recorded. The database established for ecosystem dynamics, succession, and vegetation zonation at Bintuni Bay Nature Reserve is an important tool in future management of the conservation area. Â© 2008 Jurusan Biologi FMIPA UNS Surakarta Key words: mangrove ecosystem, GIS, Bintuny bay.